Elevated transaminase levels in the postoperative period: sevoflurane re‐exposure?. Issue 1 (21st May 2013) - Tympa, Aliki; Bekiari, Altana; Kotsis, Thomas; Staikou, Chryssoula
Summary: Drug‐induced liver injury can be a life‐threatening complication, especially when it occurs in the peri‐operative setting. The cause of hepatic damage is not always clear and the underlying pathophysiology may be complex. We report a case of a female vascular surgical patient who developed a 27‐fold increase in liver enzymes with mild clinical symptomatology following left carotid endarterectomy under general anaesthesia. The patient had previously undergone right carotid endarterectomy in the same institution 35 days earlier when she had received the same anaesthetic and analgesic regimen without any adverse effects. In the present case, the cause of subclinical liver injury remains uncertain. We suggest that sevoflurane re‐exposure along with an idiosyncratic liver reaction might have resulted in the large increase in serum glutamic‐oxaloacetic transaminase (SGOT) and serum glutamic‐pyruvic transaminase (SGPT) values.